A hapten design strategy to enhance the selectivity of monoclonal antibodies against malachite green - Wu, Min-Fu; Xu, Nuo; Li, Sha; Huang, Yi-Lan; Wu, Min-Hua; Li, Jia-Dong; Chen, Ri-Sheng; Xiong, Wen-Ming; Li, Yong-Jun; Lei, Hong-Tao; Huang, Xin-An; Xu, Zhen-Lin (Frontiers in Sustainable Food Systems, 2024)
Malachite green (MG), a triphenylmethane dye, is used in the aquaculture industry as a disinfectant and insect repellent due to its potent bactericidal and pesticidal properties. However, its use poses potential environmental and health risks. This study analyzed and designed two haptens using computer simulation. Serum data confirmed the feasibility of introducing an arm at the dimethylamine group. Subsequently, a highly selective monoclonal antibody strain was successfully prepared based on the hapten. After optimizing the working conditions of indirect competitive enzyme-linked immunosorbent assay (IC-ELISA), the IC50 value was 0.83 ng/mL, with a detection limit (IC10) of 0.08 ng/mL and a linear range of 0.19-3.52 ng/mL. The developed monoclonal antibody exhibited a crossover rate of less than 0.1% with other similar structures and can be used to establish an immunoassay.